Chemical pleurodesis by small bore catheter in hepatic hydrothorax: A feasibility study - Asem A. Hewidy; Nasef Abdelsalam A. Rezk; Ahmed Abdel-Razik (Egyptian Journal of Chest Disease and Tuberculosis, 2016)
Background: Hepatic hydrothorax treatment remains problematic, and chemical pleurodesis can be considered. Objectives: The aim of this study is to compare the efficacy and safety of chemical pleurodesis by small bore catheter to tube drainage in hepatic hydrothorax. Methods: A randomized clinical study included 30 patients with hepatic hydrothorax who were admitted to Chest Department, Mansoura University Hospital, Egypt from 2011 to 2014. Patients diagnosed with exudative effusion, renal impairment, hepatic encephalopathy were excluded. Patients were divided into 2 groups; group A (20 patients) managed by small catheter and group B (10 patients) managed by intercostal tube, chemical pleurodesis in both groups was done by Viscum. Clinical, radiological data and hospital stay duration were adopted for comparison between both groups. Results: Pleurodesis was successful in group A 65% (13 patients) and in group B 70% (7 patients). Hospital stay duration was 10 days for group A and 11 days for group B. Post procedure chest pain score was less in group A than group B which was statistically significant. No serious complications and no mortality occured. Conclusions: Small bore catheter chemical pleurodesis has successful outcome, less post procedure chest pain and minimal complications in refractory hepatic hydrothorax.